2019
DOI: 10.1155/2019/5069578
|View full text |Cite
|
Sign up to set email alerts
|

miR-129-5p Inhibits Adipogenesis through Autophagy and May Be a Potential Biomarker for Obesity

Abstract: Introduction Obesity has an unclear pathogenesis. MicroRNAs (miRNAs) may function as biologically active molecules for obesity through regulating adipocyte differentiation. This study aimed to identify how miR-129-5p (a specific miRNA) regulates adipogenesis in vitro and explore its possible role in the pathogenesis of obesity in humans. Materials and Methods The miR-129-5p expression was detected in obese mouse models. The effect of miR-129-5p on adipocyte differentiation was observed, and the adipose markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…As expected, downregulation of miR-129-5p reversed the in uence of NAFLD on lipid metabolism and insulin sensitivity in NAFLD mice model. Supportably, in obese mouse models, miR-129-5p is suggested to be highly expressed in the white adipose tissue of model mouse and inhibits the differentiation of brown fat adipogenesis, which contributes to obesity and development of IR [15]. Combining the presents results and previous evidence, we concluded that the regulatory effect of miR-129-5p on NAFLD may function by regulating lipid accumulation and insulin sensitivity.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As expected, downregulation of miR-129-5p reversed the in uence of NAFLD on lipid metabolism and insulin sensitivity in NAFLD mice model. Supportably, in obese mouse models, miR-129-5p is suggested to be highly expressed in the white adipose tissue of model mouse and inhibits the differentiation of brown fat adipogenesis, which contributes to obesity and development of IR [15]. Combining the presents results and previous evidence, we concluded that the regulatory effect of miR-129-5p on NAFLD may function by regulating lipid accumulation and insulin sensitivity.…”
Section: Discussionsupporting
confidence: 77%
“…Consistently, elevated expression of miR-129-5p has been reported in subjects with obesity and serves as a promising biomarker for the occurrence of obesity, which contributes to the development of NAFLD [15]. In addition, miR-129-5p has also been demonstrated to be involved in the process of metabolic diseases, such as diabetes mellitus, islets damage [23,24].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This miRNA targets both Igf2 (insulin like growth factor 2) and Egr1 (Early growth factor response 1), with both these factors being UCP1 inhibitors [ 92 , 112 ]. A recent study by Fu et al showed that MiR-129 also directly targets ATG7 (Autophagy-related gene 7), which is an essential autophagy gene [ 89 ]. Indeed, this study showed that MiR-129-5p inhibits adipogenesis by autophagy, demonstrating increased expression of MiR-129-5p in the AT of db / db mice.…”
Section: Micrornas In Batmentioning
confidence: 99%
“…Autophagy, as a basic biological process that degrades and recycles damaged organelles and intracellular macromolecules, participates in multiple pathological and physiological processes. It has been documented that autophagy takes part in the progression of various diseases, such as neurodegenerative disorders (Kumar et al, 2018), diabetes (Barlow and Thomas, 2015), obesity (Fu et al, 2019), and so on. Notably, growing evidence has indicated that autophagy is also involved in many ischemic diseases, including myocardial infarction (Aisa et al, 2017), renal ischemia reperfusion injury (Hou et al, 2019), and cerebral ischemia reperfusion injury (Zhang et al, 2013), etc.…”
Section: Introductionmentioning
confidence: 99%